Color naming in Africa - (:unkn) unknown (My University, 2019)
This chapter is the first large-scale typological survey of the lexical means used in African languages to express color-related meanings. It is based on a very large sample, with data from 350 languages, most of which come from the RefLex online lexical database. It focuses on semantic and morphosyntactic strategies as well as contact induced strategies used for color naming. After a discussion of the issues raised by “basic” color terms, and “polychromatic” color terms, the chapter provides a review of the semantic sources of color terms, the origin of borrowings, colexifications and metaphorical uses of NPs, main patterns of lexicalization, and, briefly, ideophones.
Keywords: African Research